Prototheca zopfii Colitis in Inherited CARD9 Deficiency. (6th April 2018) - Sari, Sinan; Dalgic, Buket; Muehlenbachs, Atis; DeLeon-Carnes, Marlene; Goldsmith, Cynthia S; Ekinci, Ozgur; Jain, Dhanpat; Keating, M Kelly; Vilarinho, Silvia
Abstract : Human protothecosis is a rare microalgae infection, and its dissemination typically occurs in immunocompromised individuals. We describe a child with Prototheca zopfii pancolitis who harbors a novel recessive frameshift mutation in CARD9, suggesting a new mechanistic insight into anti- Prototheca immunity. Abstract: Human protothecosis is a rare microalgae infection, and its dissemination typically occurs in immunocompromised individuals, but no specific immune defect has been reported. Here, we describe an 8-year-old daughter of a consanguineous union with abdominal pain and bloody diarrhea for 3 months who was found to have pancolitis with numerous microalgae identified as Prototheca zopfii . In the absence of a known immunodeficiency, exome sequencing was performed, which uncovered a novel recessive frameshift mutation in CARD9 (p.V261fs). This report highlights that CARD9 deficiency should be investigated in patients with unexplained systemic/visceral protothecosis and suggests a new mechanistic insight into anti- Prototheca immunity.